Detección de mastitis subclínica en producción lechera mediante métodos cuantitativos y cualitativos, en hatos del departamento del cauca (2021)
The main objective of the following study focused on detecting subclinical mastitis by qualitative and quantitative methods with CMT tests (California mastitis test), physical-chemical analysis and somatic cell count. The research was carried out in 6 cattle herds in the department of Cauca. The choice of this topic was due to the economic importance of subclinical mastitis and the need to make farmers aware of the situation of subclinical mastitis on their farms. Through a descriptive cross-sectional study, 61 raw milk samples were taken to determine some physicochemical and somatic cell count parameters. The data obtained were analyzed according to the regulations in force in Colombia (Decree 616 of 2006) of the Ministry of Social Protection. Most of the physicochemical parameters of the raw milk samples evaluated were found to be outside the normal parameters of Colombian legislation. Somatic cell count was also higher than allowed. Raw milk has poor physicochemical quality which is directly related to the somatic cell count. The presence of subclinical mastitis is determined in all herds and good milking practices are recommended.